2015
DOI: 10.1038/jcbfm.2014.247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoacylglycerol Lipase Prevents Chronic Traumatic Encephalopathy-Like Neuropathology in a Mouse Model of Repetitive Mild Closed Head Injury

Abstract: Following the online publication of this article, the authors noticed that the labeling in panel C (Latency and Velocity) within Figure 6 was incorrect: the dark green bar in the latency graph relates to TBI-JZL and in the velocity graph relates to TBI-Veh; the red bar in the latency graph relates to TBI-Veh and in the velocity graph relates to TBI-JZL. The authors regret any confusion caused by this labeling error.In addition, the authors wish to add a sentence regarding calculation of the velocity (swimming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Previous studies have highlighted the anti-inflammatory effects of MAGL inhibition in acute and chronic brain insults and transgenic mouse models [ 10 , 11 , 23 , 24 ]. Additionally, the protective role of 2-AG in preserving BBB integrity after acute brain injury has been described [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have highlighted the anti-inflammatory effects of MAGL inhibition in acute and chronic brain insults and transgenic mouse models [ 10 , 11 , 23 , 24 ]. Additionally, the protective role of 2-AG in preserving BBB integrity after acute brain injury has been described [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…One report showed an increase in neuronal tau immunoreactivity ( 31 ) and another showed elevated amyloid precursor protein (APP) ( 13 ) at a variety of time points post-injury. A final study by Zhang and colleagues showed that monoacylglycerol lipase can lead to behavioral deficits and tauopathy characteristic of a CTE-like phenotype ( 32 ). These findings were further verified in other studies using transgenic models of amyloidosis and tauopathy in which repetitive injury paradigms produced elevated amyloid and tau levels with increased deposition.…”
Section: Implications For Modeling Cte: Results From Prior Cte Modelimentioning
confidence: 99%
“…For this reason, it has yet to be determined exactly how TDP-43 aggregates coincide and interact with pathological p-Tau accumulation. Overall, few mouse studies have sought to evaluate TDP-43 pathology after closed-head TBI [ 1 , 13 , 73 , 78 ]. Here, we found widespread TDP-43 expression following rTBI with a persistent presence of cytoplasmatic mislocalization by 6 months post rTBI.…”
Section: Discussionmentioning
confidence: 99%